A review on the effect of crumb rubber addition to the rheology of crumb rubber modified bitumen - Ibrahim, M.R.; Katman, H.Y.; Karim, M.R.; Koting, S.; Mashaan, N.S. (2013)
Crumb rubber modification has been proven to enhance the properties of pure bitumen. This paper looks at some of the international standards for producing crumb rubber modified bitumen (CRMB) and reviews the effect of crumb rubber to the rheology of crumb rubber modified bitumen. The review shows that the rheology of CRMB depends on internal factors such as crumb rubber quantity, particle size, and pure bitumen composition, and external factors such as the mixing time, temperature, and also the modification technique. These factors govern the swelling process of crumb rubber particles that lead to the increase of viscosity of the modified bitumen. However, the mixing temperature and duration can cause rubber particles to depolymerize and subsequently cause loss of viscosity. Crumb rubber modification also improves the properties of bitumen by increasing the storage and loss modulus and enhancing the high and low temperature susceptibility. The effect of crumb rubber to aging properties of CRMB is also discussed. Finally several techniques of chemical modification to terminal blends of CRMB and the subsequent improvement to the settling property of CRMB are explained.